(3ebOeIs ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3hGYde HCf CUd gPG GdHGH eQLYg Yf Chdj GdCdHGH s
(3BNQgG (B:s
(3GfJgi HMeO Gddg JYGdi hMSf Yhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg eGdc (B411) s
Keywords: (3Gdabg GdeGdcjs